Genetic variation in the grafted vegetatively propagated mango (Mangijera indica) - Gan, Yik Yuen; Sultan, Zaini; Abdol, Idris (1981)
The purpose of this project is to study the authenticity of the naming system of the bud grafted mango (Mangifera indica) .. Many type of mango are commonly cultivated, namely, Apple, Malgoa, Harum~anis, Erwin, etc. Regarding the naming system, there are two schools of thought. One suggests that the different types are different' clones'. The other view is that they are different 'varieties'. Since a clone is defined as a group of plants or individuals propagated asexually from a single parent, their isozyme patterns should be uniform or identical. If the isozyme patterns of plants that reputedly belong to the same clone show a high degree of variation between individuals, this would indicate that they are not a true clone. Six'clones' of mango were studied using the electrophoretic technique. The banding patterns of four enzyme systems including esterases, aspartate aminotransferase and acid and alkaline phosphatases were analysed. From the results obtained, it is suggested that the term 'variety', rather than the term'clone' is more appropriate. The results suggested that all the morphologically similar individuals of the same'clone' in fact do not come from the same parent. The present chaotic naming system of mango should be standardised and improved so that it can be used as a basis for plant breeding research.